MENGENALKAN KONSEP ANGKA 1-10 MELALUI PERMAINAN TRADISIONAL ENGKLEK - Aisyah Aisyah (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2022)
The research is motivated by the low ability of children to recognize numbers 1-10. From the results of preliminary observations children are still experiencing difficulties and still need help in recognizing numbers. For this reason, playing activities using traditional Engklek games are used as a means of introducing the concept of numbers 1-10. This study aims to determine the effect of traditional engklek games on the introduction of the concept of numbers 1-10 in group A RA Darussalam Jogosatru Sukodono Sidoarjo. The method with the research subject was Group A RA Darussalam Josgosatru Sukodono Sidoarjo, consisting of 29 children. The type of research used is pre-experimental design. With the design of “One Group Pretest and Post Test Design”. Data collection techniques using Observation, Tests, and Documentation. The data analysis techniques using the t test. Based on the results of the t-test analysis it can be seen that the value of the t-test (5,116) and than the t-table value is (2.048) with a significance level of 0,05%. From these results it can be seen that the value of t-count > t-table, so that H0 is rejected and Ha is accepted. So it can be concluded that there is the influence of traditional Engklek games on the introduction of the concept numbers 1-10 in group A RA Darussalam Jogosatru Sukodono Sidoarjo